Community-based participatory design of a psychosocial intervention for migrant women in Ecuador and Panama - M. Claire Greene; Annie Bonz; Rachel Isaacs; Maria Cristobal; Carolina Vega; Lena S. Andersen; Alejandra Angulo; Andrea Armijos; María Esther Guevara; Lucia Benavides; Alejandra de la Cruz; Maria Jose Lopez; et al. (Elsevier, 2022)
There is increasing evidence supporting the effectiveness of scalable mental health and psychosocial support (MHPSS) interventions delivered by non-specialists for improving wellbeing among migrant populations in humanitarian settings. Balancing fidelity in the implementation of evidence-based MHPSS interventions with their fit to the needs and preferences of new populations and contexts remains a challenge when introducing MHPSS interventions in new settings. This paper describes a community-based participatory approach to MHPSS intervention design incorporating processes to promote local adaptability and fit while maintaining standardized elements of existing MHPSS interventions. We conducted a mixed-methods study to design a community-based MHPSS intervention that fit the mental health and psychosocial needs of migrant women in three sites in Ecuador and Panama. Drawing from a set of community-based participatory research methods, we identified the priority mental health and psychosocial needs among migrant women, co-developed intervention mechanisms that aligned with those needs, matched mechanisms to existing psychosocial intervention components, and iteratively piloted and refined the intervention with community stakeholders. The resulting intervention was a five-session, lay facilitator-delivered group intervention titled, Entre Nosotras ('among/between us'). The intervention combined elements of individual and community problem solving, psychoeducation, stress management, and social support mobilization to address prioritized problems including psychological distress, safety, community connectedness, xenophobia and discrimination, and social support. This research outlines an emphasis on the social dimension of psychosocial support, as well as a process for balancing fit and fidelity in intervention design and implementation.